Precautionary and entrepreneurial saving: new evidence from German households - Frank M. Fossen; Davud Rostam-Afschar (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The well-documented positive correlation between income risk and wealth was interpreted as evidence for high amounts of precautionary wealth in various studies. However, the large estimates emerged from pooling non-entrepreneurs and entrepreneurs without controlling for heterogeneity. This paper provides evidence for Germany based on representative panel data including private wealth balance sheets. Entrepreneurs, who face high income risk, hold more wealth than employees, but it is shown that this is not due to precautionary motives. Entrepreneurs may rather save for old age, as they are usually not covered by statutory pension insurance. The analysis accounts for endogeneity of entrepreneurial choice.
Keywords: D91; D12; E21; 330; Precautionary saving; precautionary wealth; entrepreneurship; Sparen; Vermögensbildung; Kassenhaltungsansatz; Privater Haushalt; Unternehmer; Selbstständige; Berufswahl; Deutschland